1976
DOI: 10.1128/jvi.18.2.445-453.1976
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of infectious Rous sarcoma virus production by rifamycin derivative

Abstract: A new rifamycin derivative, rifazone-82 (R-82), an inhibitor of viral RNA-dependent DNA polymerase, is selectively toxic to transformed chicken cells in culture. R-82 has now been shown to possess antiviral activity as well. The relatively nontoxic properties of R-82 to nontransformed cells have permitted the execution of experiments examining the effect of a rifamycin derivative on virus reproduction. Addition of low concentrations of R-82 (15 mug/ml) to cultures soon after Rous sarcoma virus infection preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Some rifamycin derivatives have been found to be effective against difficult‐to‐treat M. avium and M. intracellulare infections in patients with AIDS [2], and against pneumococci with decreased susceptibility to penicillin [3]. Rifamycins with lipophilic side chains were found to be active at higher concentrations against RNA tumor viruses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some rifamycin derivatives have been found to be effective against difficult‐to‐treat M. avium and M. intracellulare infections in patients with AIDS [2], and against pneumococci with decreased susceptibility to penicillin [3]. Rifamycins with lipophilic side chains were found to be active at higher concentrations against RNA tumor viruses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some rifamycin derivatives have been found to be e¡ective against di¤cult-to-treat M. avium and M. intracellulare infections in patients with AIDS [2], and against pneumococci with decreased susceptibility to penicil-lin [3]. Rifamycins with lipophilic side chains were found to be active at higher concentrations against RNA tumor viruses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rifampin inhibits poxvirus replication in vitro via a mechanism other than inhibiting DNA-dependent RNA polymerase. In vitro screening for selective inhibition of RNA-dependent DNA polymerase (reverse transcriptase) on a number of derivatives revealed that certain derivatives prevented focus formation by RNA tumour viruses (Szabo et al 1976). Rifamycin derivatives were also found to act against type II DNA topoisomerases.…”
Section: Rifamycinsmentioning
confidence: 99%